2013
DOI: 10.1080/15533174.2012.740737
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Theoretical Study of Nanoparticles of Triphenylphosphonium Tetrachloroaluminate(III) [P(C6H5)3H]+[AlCl4]

Abstract: Triphenylphosphonium tetrachloroaluminate(III) [P(C 6 H 5 ) 3 H] + [AlCl 4 ] − , TPPTCA, nanoparticle was synthesized by using triphenylphosphonium chloride addition to AlCl 3 in the presence of surfactant. The product was characterized by spectroscopic and analytical methods such as 31 P-NMR, FT-IR, XRD, SEM, and CHN. Theoretical calculations were used for the structural optimization of this compound. The structure of compound has been calculated and optimized by the density functional theory (DFT) based meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Theoretical studies on pyridinium-based ILs by Zhang′s group and Guan′s group have shown that the anion was primarily located above, below, and on both sides of the pyridine ring plane, and liquid-phase calculation reduced the interionic interaction. For phosphonium or aluminum-based ILs, only their structural data and comparisons between experimental and simulated infrared spectra were explored.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies on pyridinium-based ILs by Zhang′s group and Guan′s group have shown that the anion was primarily located above, below, and on both sides of the pyridine ring plane, and liquid-phase calculation reduced the interionic interaction. For phosphonium or aluminum-based ILs, only their structural data and comparisons between experimental and simulated infrared spectra were explored.…”
Section: Introductionmentioning
confidence: 99%